PENGEMBANGAN ALAT EVALUASI ONLINE MENGGUNAKAN WONDERSHARE QUIZ CREATOR PADA MATERI BENTUK MOLEKUL DI KELAS X IPA - Noer Hidayatullah; Rachmat Sahputra; Ira Lestari; Rahmat Rasmawan; Rody Putra Sartika (EduChem, 2023)
The problem that arises in this study is that the assessment carried out by the teacher takes a relatively long time because of the manual calculation of points.Â  Then the teacher tends to make the same questions for all students, it makes it easier for students to collaborate. This study aims to determine the feasibility of an online evaluation tool using wondershare quizcreator on molecular shape materials. The form of this research is research and development (R&D) based on the steps of the ADDIE development model. The online evaluation tool using Wondershare Quizcreator on molecular shape material has been tested for feasibility by experts, including the feasibility of the material, language, and graphics. The expert feasibility test results show that the developed online evaluation tool is categorized as very feasible. This feasibility is viewed from the results of the validation of the feasibility of the material by 95.6%, the feasibility of language by 90.63%, and the feasibility of graphics by a percentage of 94.64%.